Nomad citizenship : free-market communism and the slow-motion general strike - Holland, Eugene W. (University of Minnesota Press, 2011)
Nomad Citizenship argues for transforming our institutions and practices of citizenship and markets in order to release society from dependence on the state and capital. It changes Deleuze and Guattari's concept of nomadology into a utopian project with immediate practical implications, developing ideas of a nonlinear Marxism and of the slow-motion general strike. Responding to the challenge of creating philosophical concepts with concrete applications, Eugene W. Holland looks outside the state to analyze contemporary political and economic development using the ideas of nomad citizenship and.